Memahami Dampak Greenflation terhadap Dinamika Harga Konsumen: Analisis Komparatif - Surya Bakti; Hadi Suriono; Durahman Marpaung; Lukman Nuzul Hakim (Departement of Mathematics Education, 2024)
This article discusses the impact of greenflation on consumer price dynamics. Greenflation is a phenomenon that arises from the global drive towards sustainability, where increased demand for environmentally friendly products and technologies can lead to price increases due to higher production costs or limited availability. This study uses a literature review method to analyze the direct and indirect impacts of greenflation on consumer prices and compares these impacts across various countries or economic sectors. The research findings show that investments in green technology, environmental regulations, and changes in supply chains can increase production costs and final product prices. Direct impacts of greenflation include rising energy and transportation costs, as well as higher prices for goods and services produced with stricter environmental standards. A comparison between developed and developing countries indicates that developed countries have greater resources to invest in green technology but also experience more significant greenflation. This article provides insights into effective ways to manage the impacts of greenflation, including the implementation of policies supporting sustainable business practices, fiscal incentives for green technology, and strict enforcement of environmental regulations.